2012
DOI: 10.1038/pr.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Lung hypoplasia in rats with esophageal atresia and tracheo–esophageal fistula

Abstract: IntroductIon: survivors of esophageal atresia and tracheo-esophageal fistula (ea-TeF) often suffer chronic respiratory tract disease. ea-TeF results from abnormal emergence of the trachea from the foregut. This study in a rat model tests the hypothesis that primary lung maldevelopment might be a downstream consequence of this defect. results: The lung was hypoplastic in rats with ea-TeF although the histological pattern was normal. Maturation and arteriolar wall thickness were unchanged, but mesenchymal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…In the trachea, malformed and deficient cartilage has been described, and correlation of these findings with the high rate of tracheomalacia afflicting neonates with OA/TOF was intimated Pole et al, 2001]. The lungs of treated embryos were hypoplastic and had decreased airway branching; however, histological findings were similar to controls [Xiaomei et al, 2012]. Other tracheo-oesophageal anomalies including foregut duplications and bronchopulmonary foregut malformations, such as an ectopic lung or bronchus arising from the oesophagus, are reported in the model, indicating these may have a similar developmental aetiology to OA/TOF in the ARM [Qi and Beasley, 1999b;Qi et al, 2001].…”
Section: Observations Of Phenotype Of the Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…In the trachea, malformed and deficient cartilage has been described, and correlation of these findings with the high rate of tracheomalacia afflicting neonates with OA/TOF was intimated Pole et al, 2001]. The lungs of treated embryos were hypoplastic and had decreased airway branching; however, histological findings were similar to controls [Xiaomei et al, 2012]. Other tracheo-oesophageal anomalies including foregut duplications and bronchopulmonary foregut malformations, such as an ectopic lung or bronchus arising from the oesophagus, are reported in the model, indicating these may have a similar developmental aetiology to OA/TOF in the ARM [Qi and Beasley, 1999b;Qi et al, 2001].…”
Section: Observations Of Phenotype Of the Modelmentioning
confidence: 85%
“…Between 28% and 93% of ARM embryos have tracheooesophageal malformations [Diez-Pardo et al, 1996;Merei et al, 1997b;Qi et al, 2001;Gillick et al, 2003;Xiaomei et al, 2012]. A spectrum of these anomalies have been described in the ARM, the near-term embryo most frequently (80%) displaying an upper OA pouch with distal TOF .…”
Section: Observations Of Phenotype Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that rat fetuses with esophageal atresia and tracheoesophageal fistula induced by adriamycin have hypoplastic lungs and abnormal control of branching with FGF10 (fibroblast growth factor 10) overexpression in the pseudoglandular, canalicular, and saccular stage of lung development (22,23).…”
Section: Lungs From Fetuses Exposed To Adriamycin Without Ea-tefmentioning
confidence: 99%
“…Adriamycin-induced EA-TEF is associated with defective tracheobronchial branching and some degree of lung hypoplasia (22,23). The present study examined whether the abnormal foregut expression pattern of Shh at the site of emergence of the tracheobronchial bud is translated into the developing lung of rats with EA-TEF/VACTERL association.…”
mentioning
confidence: 99%